Study of the Microstructure of 20 GL Steel Samples Cut From A WedgeShaped and Side Frame After Volumetric Surface Quenching - Eshboboev Sardor Nurbobo ugli; Rakhmatov Sirozhiddin Eshmakhmadovich; Nurolliev Novruz Shoymardon ugli; Inatillayeva Khusnora Askar qizi (Genius Publishing Group, 2022)
This work is devoted to the topic ” Study of the microstructure of 20 GL steel samples cut from a wedge-shaped and side frame after volumetric surface hardening".
Keywords: Volume-surface quenching; quenching; wedge-shaped; bolster